Sports marketing innovation: increasing fan engagement via innovative statistics from facial emotion recognition - Kröckel, Pavlina; Piazza, Alexander; Wessel, Pascal (4th International Conference Business Meets Technology (BMT22), 2022)
Technology in football is increasingly used for decision making. Adoption, especially in Germany, has been slow. However, the benefits of data analytics for pre-, and post-match analysis have motivated decision makers to pay attention to the data science trend. Nowadays, football clubs from the third leagues or even amateur clubs are using technology to help them gain a competitive edge. Fan experience, both online and offline (home in front of the TV or at the stadium) is driving the next innovation stage in football. The study presented here is focused on testing and evaluation a facial recognition software on images from football coaches, just a few seconds after an important situation during the match has taken place (e.g., win, goal scored). We demonstrated that, in fact, emotion recognition software captures unexpected emotional reactions from coaches which could then be used to calculate interesting statistics and increase fan engagement and entertainment.<br
Keywords: Emotion recognition; Football; Soccer; Ffan; Fan engagement; Sports marketing